Proteomic analysis of physiological function response to hot summer in liver from lactating dairy cows. (April 2017) - Wang, Qiangjun; Zhao, Xiaowei; Zhang, Zijun; Zhao, Huiling; Huang, Dongwei; Cheng, Guanglong; Yang, Yongxin
Abstract: Lactation performance of dairy cattle is susceptible to heat stress. The liver is one of the most crucial organs affected by high temperature in dairy cows. However, the physiological adaption by the liver to hot summer conditions has not been well elucidated in lactating dairy cows. In the present study, proteomic analysis of the liver in dairy cows in spring and hot summer was performed using a label-free method. In total, 127 differentially expressed proteins were identified; most of the upregulated proteins were involved in protein metabolic processes and responses to stimuli, whereas most of the downregulated proteins were related to oxidation–reduction. Pathway analysis indicated that 3 upregulated heat stress proteins (HSP90α, HSP90β, and endoplasmin) were enriched in the NOD-like receptor signaling pathway, whereas several downregulated NADH dehydrogenase proteins were involved in the oxidative phosphorylation pathway. The protein–protein interaction network indicated that several upregulated HSPs (HSP90α, HSP90β, and GRP78) were involved in more interactions than other proteins and were thus considered as central hub nodes. Our findings provide novel insights into the physiological adaption of liver function in lactating dairy cows to natural high temperature. Highlights: Changes in liver proteome expression of dairy cows are responsed to hot summer. Increased proteins involved in protein metabolic process and response to stimulus. Decreased proteins related to the oxidation reduction. HSPs were considered as "crosstalk" nodes in the protein-protein interaction (PPI) networks. These findings provide a useful resource for exploring the adaption mechanisms of the liver to environmental high temperature stress.